"A Book of Stone to Make Spain’s Matters Known" – Madrid’s Palacio Nuevo and the Old Rome between Philip V and Charles III - Panzram, Sabine (Medieval encounters, 2025)
In 1734, the Real Alcázar in Madrid burned to the ground. The construction of the Palacio Nuevo there - today known as the Palacio Real - forced Philip V to rethink his self-image: a task with which he entrusted to the Benedictine Martín Sarmiento. With his so-called Sistema de adornos del Palacio Real (1743), he proposes a form of representation in order to showcase the Catholic and secular virtues of the Spanish monarchy since ancient times. The palace was intended to become a "lieu de memoire" from which Spain could be "contemplated." The didactic impetus is obvious. When Charles III took power in 1759, he ordered the work to be stopped. There is great incomprehension when it becomes clear that he, too, is interested in ancient Rome. But, Charles III, the "rey arqueólogo" under whom Pompeii and Herculaneum were discovered, had very different ideas about the function of antiquity than his predecessor. His aim was not to establish national continuity, but to formulate a universal claim to his rule. Using the example of a paradigmatic building in Madrid, the paper seeks to grasp the significance of antiquity for concepts of rule in eighteenth-century Spain.